Paradigm for product design conceptualization using case based reasoning - Leow, Kevin Jun En. (2010)
With the increase in received competition and slowing down in technological advancement, the shift in manufacturers’ focus on redesigning existing products to reduce lead time to market has put CBR (Case Based Reasoning) in the limelight, thus expanding the demand for its applications. Conventional CBR systems promote the revision of existing idea to satisfy the current design requirements, but often lacks of the collaborative aspect of the existing web-based manufacturing systems. This report describes the concept of a web-based CBR system and its impact on the roles of the typical case based reasoning system in the product design conceptualization. In addition, the integration of the web technology through AJAX (Asynchronous JavaScript and eXtensible Markup Language) and SQL (Structured Query Language) databases contributed to the new paradigm for the CBR system. Through the implementation of the distributed CBR system, it depicted how the processing capability of the CBR functions transcends geographical boundaries in the context of light fixture design. Despite the domain specific application, the processing capability can be expanded to include other categories of product designs due the flexibility of the system. Improvement to product design quality and reduction in time-to-market are some of the benefits yielded through the utilization of the distributed CBR system, bridging the communication gaps between the designer and engineers. The limitations of this web-based CBR system are discussed and potential research areas such as multimedia data mining, extensive 3D model handlers and clustering of case bases are identified as an improvement to the current CBR system.